CORROSION OF WELD AREA AT INTERNAL SURFACE OF PIPELINE USED IN OIL AND GAS INDUSTRY - Azam, M.A.; Abdullah, M.F.; Shimoda, T. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The objective of this work was to investigate the cause of failed pipeline steel, in particular at its weld area which may due to the preferential corrosion. The pipeline sample was supplied by an industry based in Miri, Sarawak. The serious circumstances in the piping scheme led to high-level corrosion of the inner surface, particularly in the weld region. Inside the pipe system, natural gas flowed into the processing operation within the platform. Several tests and experiments were elucidated to comprehend the metallographic of the failure portion in order to explore the failure. Pipe sample testing techniques such as visual inspection, optical microscope, scanning electron microscope, and Vickers hardness testing were carried out effectively. The characterization of the microstructure was carried out on the sample taken from three main regions of the sample, which are the base metal, the heat affected area and also the weld joint, in order to elaborate the difference of the properties. The test outcome has shown that corrosion occurred at the pipe, even though the pipe system used cathodic protection.